The Application Of Branding Concepts In Tourism Villages: Building Local Destination Identity In Banyubiru Subdistrict, Semarang Regency - Siti Juriah; Nugroho , Nugroho (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines the application of branding concepts in the development of tourism villages in Banyubiru District, Semarang Regency. Tourism villages as a form of community-based tourism require appropriate branding strategies to build strong and sustainable destination identities. This descriptive qualitative research used data collection techniques through observation, in-depth interviews, and documentation studies involving local stakeholders. The results show that the application of branding concepts has succeeded in increasing tourist awareness and local community participation, although some challenges were found in implementation consistency. The development of local destination identity through a branding approach has proven to contribute to increasing tourist visits and village economic sustainability. This research recommends strengthening branding strategies through community involvement and managing local assets as elements of differentiation.